MANAGEMENT OF QUALITY MAPPING UNITS AND PKBM PROGRAMS - Oong Komar; Nunu Heryanto; Cucu Sukmana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
The implementation of the quality mapping program for PKBM units answers the facts of the problems that often occur in every non-formal institution, especially problems in institutional operations. Based on the preliminary study, the reasons that often raised by PKBM managers are the costs for institutional operations, the competence of educators who do not understand the andragogy approach in the learning implementation, then the concern of the government in the world of non-formal education. This study was based on the analysis of community needs. This study aims to describe the quality management of the PKBM units and programs that emphasize the principles of managing community education programs. To reveal the data and information, the researchers applied a descriptive study with a qualitative approach, namely revealing the depth of data and information based on the research formulation and the research questions, that is how to manage the quality mapping of the unit and the PKBM program? The program management is divided into three stages, namely, the planning, implementation, and evaluation stages. Each stage in its implementation always begins with analyzing needs, then compiling a recommended forum design with the development of discussion materials, then ending with an evaluation.